Certainty Planning in an Uncertain World: A Reconsideration - Danthine, Jean-Pierre; Donaldson, John B. (Review of Economic Studies, 1981)
Jean-Pierre Danthine, John B. Donaldson; Certainty Planning in an Uncertain World: A Reconsideration, The Review of Economic Studies, Volume 48, Issue 3, 1